Governança no setor público: uma análise nas universidades federais da região Centro-Oeste do Brasil à luz das dimensões e princípios internacionais - Silveira, Vanessa Cristina dos Anjos (2024)
Although public governance is an ally of management, seeking improvements in the provision of services with a focus on citizens and organizational performance, little research explores governance practices in higher education institutions. In this context, the present work aims to identify the level of adherence, analyzing the practices least adopted by federal universities in the Midwest region in relation to the dimensions and principles of governance recommended by international institutions, in order to propose a guide for implementing governance practices. To this end, through applied research, with an exploratory-descriptive objective following the quantitative approach, a survey was applied to five public universities in the Central-West region with the purpose of measuring the percentage of adherence to governance practices, according to two international frameworks, Good Governance in The Public Sector and Study 13. In the qualitative approach, we sought to identify the practices adopted through the analysis of institutional documents and bibliographical survey, according to the Study 13 framework. The results showed that in both frameworks, universities have a medium to high level of adherence, both in the perception of university counselors and through the application of the verification protocol. Opportunities for improvements related to practices in the behavior patterns and control dimension of the Study 13 model were also identified. As a consequence, in the end, a conclusive technical report was presented condensing the main results of this research.